Positron Annihilation Spectroscopy of Young Supernova Remnants - Doikov, D. N. (Одеські астрономічні публікації, 2018)
This paper discusses radiative and thermodynamic properties of cold rarefied aggregates of non-uniformly distributed gas and dust through which high fluxes of positrons with energies of 0.011-3.6 MeV pass. The investigated gas is in the form of a nebula with densities of 1-108 cm-3 and temperatures ranging from 30-100 K. We estimated the energy input into thermodynamic temperatures of the ejecta components. Additional heating and γ-ray luminosity of all the components of the examined ejecta were factored in. The structure of the radiation field S(E,r) and electron velocity distribution function F(E,r) were determined depending on the energies of quanta and electrons, respectively. The ejecta of SN 1987A was considered as an ideal object to investigate the positron impact on the nebula. The interaction of positrons with solids, atoms and molecules was examined separately. Traveling of positrons in solids typically results in their enhanced amorphous state, heating and annihilation with free electrons of solid-state grains with emission of two photons each of the energy . Consequently, a characteristic excessive luminescence of particles, namely astronomical silicates and graphite, occurs. In fact, the energy loss of fast positrons due to ionisation leads to consecutive creation of K-L-M vacancies, which is followed by cascade transitions with the transfer of the remaining energy to the Auger electrons rather than to surrounding atoms which make up a solid. In this case, in a solid particle, the energy released in cascade transitions is either used to change the lattice structure or converted into γ-quanta emission upon the annihilation of positrons and K-L electrons. The estimated energy used to heat a solid particle itself makes up a half of the energy released in the downward M-L-K cascades, which is indicative of a significant contribution to the energy balance of the ejecta dust. This contribution exceeds the energy estimates from the net radiation loss of particles in the matter. In the nebular atomic-molecular plasma of the supernova ejecta, the conservation of energy dictates that the energy lost to create a K-vacancy is allocated to the subsequent cascade transitions and the Auger electrons while the one-photon annihilation of positrons and K-electrons of atoms and molecules yields characteristic γ-quanta with energies close to their own values - . The study of annihilation of positrons and K-electrons with emission of a single photon revealed a relationship between the energy of the emitted γ-quanta with the recoil energies of nuclei , binding energies of K-electrons of different atoms - and energies of incident positrons . The cross-sections for interactions of positrons and atoms in the investigated young supernova remnants were calculated and scaling of electron arrangements of the atoms involved in those interactions was performed. We pointed out that for the iron-peak atoms the cross-section for the positron-atom interaction increases by four orders of magnitude, thus making the interaction between positrons and electrons in the K-L shells the most probable. It is shown that in astrophysics the positron annihilation spectroscopy of matter yielding a characteristic radiative response has opened up new opportunities for studying young supernova remnants and active galactic nuclei. In particular, it is now possible to independently determine the mass ratio of dust and gas-molecular components by the strength ratio of annihilation γ-lines I (0.511)/I (1.022). We report the estimated contribution of various elements to the profiles of the indicated γ-lines and conclude that it is not related to the proper dynamic motions of the supernova remnants. This is a crucial factor in the study of bulges in active galactic nuclei wherein the physical conditions are assumed to be steady-state in relatively large scales.